(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Vehicle detection and counting are turning out to be progressively significant in the field of Highway management. In any case, because of the various sizes of vehicles, their identification stays a test that straight forwardly influences the exactness of vehicle counts. To resolve this issue, we propose a vehicle detection system and counting framework.